Skrining Anemia Remaja Melalui Pemeriksaan Kadar Haemoglobin Dan Pemberian Tablet Fe Di Panti Asuhan Putri Muhammadiyah Tanjung - Ikhwah Muminah; Atika Nur Azizah (Universitas Muhammadiyah Klaten, 2024)
Nutritional anemia in adolescent girls is one of the causes of high death rates during childbirth and the high incidence of babies with low birth weight. The important thing in controlling anemia in pregnant women is that teenagers are able to fulfill the diversity of food substances needed by the body for the synthesis process of forming hemoglobin in the body. The aim of this activity is to carry out early detection of anemia in adolescents and administer Fe tablets as an effort to overcome anemia in adolescents. The service method used is to analyze the situation of the service location, communicate the problem to find out the public's understanding of the importance of anemia screening by checking hemoglobin levels and administering Fe tablets, determining service objectives, implementing the plan. and providing education regarding adolescent anemia and its implementation. As a result of this service, there were 10 students who experienced mild anemia. Based on the results of this examination, it is hoped that students who experience anemia and are given Fe tablets will experience an increase in their Hb levels to normal.